Psychological model of internal conflict of personality - Shapran, Tetiana (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2017)
The article contains a synonymous line of concept of "intrapersonal conflict" in the psychological literature. The characteristics of opposing forces of intrapersonal conflict interaction were discovered and described. The psychological approaches to the phenomenology of interpersonal conflict were analyzed and classified. At a theoretical level the common to any stage of personality’s formation psychological model of internal conflict were grounded.